The mechanisms of action of mitochondrial targeting agents in cancer: inhibiting oxidative phosphorylation and inducing apoptosis - Yang, Yi; An, Yahui; Ren, Mingli; Wang, Haijiao; Bai, Jing; Du, Wenli; Kong, Dezhi (Frontiers in Pharmacology, 2023)
The tumor microenvironment affects the structure and metabolic function of mitochondria in tumor cells. This process involves changes in metabolic activity, an increase in the amount of reactive oxygen species (ROS) in tumor cells compared to normal cells, the production of more intracellular free radicals, and the activation of oxidative pathways. From a practical perspective, it is advantageous to develop drugs that target mitochondria for the treatment of malignant tumors. Such drugs can enhance the selectivity of treatments for specific cell groups, minimize toxic effects on normal tissues, and improve combinational treatments. Mitochondrialtargeting agents typically rely on small molecule medications (such as synthetic small molecules agents, active ingredients of plants, mitochondrial inhibitors or autophagy inhibitors, and others), modified mitochondrial delivery system agents (such as lipophilic cation modification or combining other molecules to form targeted mitochondrial agents), and a few mitochondrial complex inhibitors. This article will review these compounds in three main areas: oxidative phosphorylation (OXPHOS), changes in ROS levels, and endogenous oxidative and apoptotic processes.